Effectiveness of martial arts exercise on anthropometric and body composition parameters of overweight and obese subjects: a systematic review and meta-analysis - Fabricio de Souza; Felipe Nunes Lanzendorf; Márcia Mendonça Marcos de Souza; Fabiana Schuelter-Trevisol; Daisson José Trevisol (BMC, 2020)
Abstract Background Obesity is considered a top public health concern, and its prevalence is growing every day. Thus, interventions to address this problem should be encouraged and further studied. In this regard, the aim of this review was to summarize the evidence of martial arts interventions to evaluate their effectiveness on the anthropometric and body composition parameters of overweight and obese subjects. Methods A systematic literature search was conducted on January 26, 2020 using the PubMed, Medline, Lilacs, Cochrane, and Scielo databases. Reference lists of eligible articles and relevant reviews have also been examined. All randomized clinical trials on martial arts that evaluated the anthropometric and body composition parameters of overweight and obese subjects were included, and a narrative synthesis of eligible studies was conducted in accordance with PRISMA guidelines. The Downs & Black checklist was used to assess the quality of the studies. This review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (identifier CRD42018086116). Results A total of 82 articles were identified from the initial search strategy. A further 2 articles were identified from the review of relevant bibliographies. Six studies encompassing 258 participants who were overweight or obese were included. Four studies reported Tai Chi practice, one study reported Kung Fu exercise, and another study reported martial arts exercise. The examined meta-analyses did not reveal significant benefits from martial arts practice over control groups after the experiment period for body mass index (− 1.34 kg/m2; 95% CI: − 2.72, 0.05), waist circumference (1.41 cm; 95% CI: − 0.72, 3.54) and percentage of body fat (− 0.75%; 95% CI: − 5.58, 4.08). Conclusion The scarcity, heterogeneity, short intervention time, small sample size, and significant methodological limitations of the available studies do not allow to conclude whether martial arts are effective in the anthropometric and body composition parameters of overweight and obese individuals. This study highlights the need for more research to assess the benefits of martial arts for overweight and obese individuals.